Genome-Wide Comparisons of Mutations Induced by Carbon-Ion Beam and Gamma-Rays Irradiation in Rice via Resequencing Multiple Mutants - Yang, Guili; Luo, Wenlong; Zhang, Jian; Yan, Xiancheng; Du, Yan; Zhou, Libin; Li, Wenjian; Wang, Hui; Chen, Zhiqiang; Guo, Tao (Frontiers in Plant Science, 2019)
Physical mutagen, such as carbon-ion beams (CIBs) and gamma-rays (GRs)，induce mutations with high frequency at a relatively low dose and are more user-friendly and environment-friendly in mutation breeding. Previous studies showed that CIBs induced large sized deletions and insertions, and chromosomal rearrangements, whereas GRs induce shorter deletions and insertions, and more frequent base substitutions. However, the difference on the genomic level between CIB- and GR-induced mutations remains to be clarified. In the present study, we re-sequence 6 mutagenized lines derived from CIB irradiation and 4 mutagenized lines derived from GRs. A total of 283 and 381 variations are induced in these mutants by CIBs and GRs, respectively, including single base substitutions (SBSs), small insertion and deletions (InDels), multiple nucleotide variants (MNVs). SBSs are the most abundant type of mutation and single base transition is the main form for SBSs. CIB-induced InDels accounted for 25.44% of the total variations, while GR-induced InDels accounted for 17.85%. On the contrary, the frequency of MNVs induced by GRs was about approximately 2.35 times that induced by CIBs, which indicates CIBs induced increased InDels, whereas GRs induced increased MNVs. Notably, multiple base deletions (≥5 bp) were induced at a much higher frequency by CIBs than by GRs. We also find mutations induced by CIBs and GRs are unevenly distributed on chromosomes. Unusual high-frequency (HF) and low-frequency (LF) mutation regions are discovered by analyzing mutations per 1Mb along the genome. The mutation frequency within the HF regions were significantly higher than the LF regions (P<0.05). A large majority of SBSs, InDels and MNVs induced by CIBs and GRs occurred in upstream and downstream regions. Our study compares difference of mutation profiles induced by the CIB irradiation and GR on rice genomes, and give some clues for understanding the mutagenesis mechanism of physical radiation and improving the mutagenesis efficiency.